Effect of food processing on glycemic response to white yam (Dioscorea rotunda) meals - Jimoh, Ahmed Kayode (Array, 2008)
Summary: Postprandial glycemic response to food can be affected by the method of food preparation. The effect of processing on yam, a staple food in Nigeria, was studied in 24 healthy non-diabetic Nigerians. The postprandial glycemic indices of peak plasma glucose (PPG), maximum increase in plasma glucose (MIPG), 2-hour postprandial plasma glucose level (2HPPG), incremental area under glucose curve (IAUGC) and glycemic index (GI) were determined for boiled yam, pounded yam and yam flour (amala) after eating a measured amount of 50 g of digestible carbohydrate as recommended by FAO/WHO. Despite undergoing more processing, amala prepared from yam flour showed better postprandial glycemic response indices as compared with other study foods. Yam flour submitted to more processing showed better indices than the other yam based product compared. Yam based products, particularly yam flour, can be recommended for diabetic Nigerians as a substitute to eating monotonous beans based products